2023
DOI: 10.1128/spectrum.04824-22
|View full text |Cite
|
Sign up to set email alerts
|

The Rice Endophyte-Derived α-Mannosidase ShAM1 Degrades Host Cell Walls To Activate DAMP-Triggered Immunity against Disease

Abstract: The specific biological niche inside host plants allows endophytes to regulate plant disease resistance effectively. However, there have been few reports on the role of active metabolites from endophytes in inducing host disease resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…1e ). In our previous study, we also reported that OsiSh-2 can trigger rice immune responses by secreting α-Mannosidase ShAM1 to digest the rice cell wall and release damage-associated molecular patterns, and cell death was also observed at 24 hpt 51 . In addition, we revealed that appropriate ferroptosis was an essential factor for OsiSh-2 colonization and shaping the mutual symbiont.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…1e ). In our previous study, we also reported that OsiSh-2 can trigger rice immune responses by secreting α-Mannosidase ShAM1 to digest the rice cell wall and release damage-associated molecular patterns, and cell death was also observed at 24 hpt 51 . In addition, we revealed that appropriate ferroptosis was an essential factor for OsiSh-2 colonization and shaping the mutual symbiont.…”
Section: Discussionmentioning
confidence: 87%
“…This induction of an immune response for indirect disease resistance is not the only contribution of ferroptosis. Our recent study showed that applying ShAM1, an α-mannosidase purified from OsiSh-2 culture supernatants, can trigger rice immune responses and improve blast resistance with a 45.9% reduction in blast disease lesion length and a 67% reduction in fungal biomass 51 . Therefore, we considered that the assistance of OsiSh-2 in disease resistance in host rice depends on multiple mechanisms, and ferroptosis is one of them.…”
Section: Discussionmentioning
confidence: 99%
“…Plants may actively recruit microbial communities that can antagonize pathogenic microbes early during their growth, and the shaping of these microbial communities may be affected by host genes (see Section 3). The activation of host immune responses by endophytes can enhance the host's resistance to pathogens [170,175]. When external pathogens invade plants, there are changes in the microbial communities in different parts of the plant.…”
Section: The Endophyte Functions As An Extension Of the Plant's Immun...mentioning
confidence: 99%